Determinants Analysis of the Incidence of Stunting in Children 1-2 Years - Levi Tina Sari; Nevy Norma Renityas; Ita Novia Sari (STIKes Patria Husada Blitar, 2021)
Stunting become a serious problem in Indonesia because it was associated with increased risk of morbidity and mortality, suboptimal brain development that delayed motor development and mental retardation. In fulfillment of family nutrition required a good knowledge about balanced nutrition. This study was an observational study with case control study design, The sampling technique used purposive sampling so that the respondents obtained were 30 toddlers at 4 posyandu. Analysis of the data used for bivariate frequency distribution, while multivariate logistic regression. Result: Obtained a significant relationship with the incidence of stunting, namely the mother's education level (Ï: 0.03; 0.621), family economy (Ï: 0.03; OR: 0.158), mother's height (Ï: 0.01: OR: 12.045), while the sex of children under five did not have a significant relationship with the incidence of stunting, namely Ï: 0.11> Î±0.05. The incidence of stunting in children aged 1-2 years is influenced by the motherâ€™s education, height of parents especially motherâ€™s, and family economic status. Mothers must know about types of food that have high nutritional value at low prices so that the nutritional adequacy of the family is fulfilled.